STATE OF THE GASTRODUODENAL ZONE IN PATIENTS WITH REACTIVE ARTHRITIS - Azadaeva K.E., Tukhtaeva N.Kh., Rakhmatullaeva G.K. (Galaxy International Interdisciplinary Research Journal, 2023)
Gastroenterology and rheumatology are very closely related disciplines. There is much in common in the occurrence and manifestations of lesions of the gastrointestinal tract in connective tissue diseases [1].